Ganjar Pranowo's Political Public Relations Approach on Tiktok in the 2024 Candidacy Process - Pascal Willhard Pardamean; Muhammad Jajuli; Erwinsyah (Program Studi S3 Ilmu Manajemen, 2023)
The General Election of the President and Vice President for the 2024-2029 term in Indonesia will soon be held. The campaign process that will be carried out by the candidates has also experienced a shift, previously using outdoor media, and the mass media is now using social media. Social Media is a medium on the internet that allows users to present themselves. Political actors must be able to convey their political messages to their supporters, either directly or through intermediaries. TikTok provides a unique feature that allows political propagandists to reach a wider audience because of its fairly new content sharing model. In this research, qualitative methodology is used as an approach or search to explore and understand a central phenomenon. The results showed that the management of communication media for Ganjar Pranowo's political image was carried out by several teams, based in Central Java and a team based in Jakarta.